2020
DOI: 10.1107/s2059798320010499
|View full text |Cite
|
Sign up to set email alerts
|

The RING domain of TRIM69 promotes higher-order assembly

Abstract: Members of the TRIM protein family have been shown to inhibit a range of viral infections. Recently, TRIM69 was identified as a potent inhibitor of Vesicular stomatitis Indiana virus infection, with its inhibition being dependent upon multimerization. Using SEC-MALLS analysis, it is demonstrated that the assembly of TRIM69 is mediated through the RING domain and not the Bbox domain as has been shown for other TRIM proteins. Using X-ray crystallography, the structure of the TRIM69 RING domain has been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Finally, we investigated the activation mechanism of Ub transfer in the higher-order TRIM72 assembly on the membrane. Speci cally, we revealed that the RING domain can be dimerized for activation, similar to other known TRIM RINGs 43,[61][62][63] . Although the monomeric TRIM72 RING domains are nearly 20 nm apart from each other in the dimer model, it is likely that the RINGs are dimerized transiently since they are located close to each other in the higher-order TRIM72 assembly on the membrane (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Finally, we investigated the activation mechanism of Ub transfer in the higher-order TRIM72 assembly on the membrane. Speci cally, we revealed that the RING domain can be dimerized for activation, similar to other known TRIM RINGs 43,[61][62][63] . Although the monomeric TRIM72 RING domains are nearly 20 nm apart from each other in the dimer model, it is likely that the RINGs are dimerized transiently since they are located close to each other in the higher-order TRIM72 assembly on the membrane (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The arrangement of the TRIM2 RING dimer is reminiscent of other TRIM dimeric RING structures, such as the constitutive dimers TRIM32 (5FEY) and TRIM69 (6YXE) or those of TRIM25 (5FER) and TRIM5α (4TKP) that show minimal self-association in solution but crystallized as dimers in complex with E2~Ub conjugates (Fig. 2c) 31,33,34 . The calculated gain in solvation free energy of TRIM2 RING dimerization is −19.8 kcal/mol, a value larger than that calculated for the constitutive RING dimers of TRIM32 (−14.7 kcal/mol) and TRIM69 (−12.5 kcal/mol) 30,33 .…”
Section: Structure Of the Active Trim2 Ring/ Ube2d1~ub Complexmentioning
confidence: 89%
“…1e ) 46 . This dimerization mode is highly conserved in the TRIM family as it has now been observed in all known crystal structures of TRIM RINGs (TRIM5α: 4TKP 46 , TRIM37: 3LRQ, TRIM69: 6YXE 55 , TRIM23: 5VZW 56 , TRIM32: 5FEY 47 , TRIM25: 5EYA 47 , 48 , TRIM21: 6S53 54 and possibly others).…”
Section: Resultsmentioning
confidence: 58%